A tale of sorcery - Colfer, Chris (Little, Brown Books For Young Reader, 2021)
Brystal Evergreen is running out of time. It's almost been a year since she made a deal with Death to find and destroy the Immortal in exchange for her life and she still hasn't found a single clue about who or where the Immortal is. And something dark and malignant has risen from deep within the earth, threatening life as we know it. To stop this new evil, the fairies and witches must work with all the kingdoms and territories, including the Righteous Brotherhood and their Army of the Dead. But is the threat more familiar than they expected? Sorcery, magic, and science collide in this thrilling third book in the Tale of Magic...series that will keep readers on the edge of their seats.